2020
DOI: 10.1182/blood.2019002314
|View full text |Cite
|
Sign up to set email alerts
|

The 14-3-3ζ–c-Src–integrin-β3 complex is vital for platelet activation

Abstract: Several adaptor molecules bind to cytoplasmic tails of β-integrins and facilitate bidirectional signaling, which is critical in thrombosis and hemostasis. Interfering with integrin-adaptor interactions spatially or temporally to inhibit thrombosis without affecting hemostasis is an attractive strategy for the development of safe anti-thrombotics. Here we show for the first time that 14-3-3ζ-c-Src-integrin-β3 complex is formed during platelet activation. 14-3-3ζ-c-Src interaction is mediated by -pirlglalnfsvfyy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…Platelets from wild type and GPIbα deficient mice were used to investigate the effect of genistein and daidzein on αIIbβ3-mediated platelet aggregation. We found that not only genistein and daidzein inhibited ADP ( Figure 3 A), collagen ( Figure 3 B), thrombin ( Figure 3 C), and arachidonic acid ( Figure 3 D) induced platelet aggregation but also high concentration of collagen ( Figure 3 E) and integrin αIIbβ3 activator anti-αIIb TM ( Figure 3 F) induced platelet aggregation, suggesting these soy isoflavones might inhibit αIIbβ3 outside-in signaling [ 22 , 30 , 31 ]. The inhibitory effect of genistein and daidzein on platelet aggregation was not through GPIb-IX signaling, since both of these compounds inhibited ADP ( Figure 3 G) and collagen ( Figure 3 H) induced platelet aggregation in GPIbα deficit platelets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelets from wild type and GPIbα deficient mice were used to investigate the effect of genistein and daidzein on αIIbβ3-mediated platelet aggregation. We found that not only genistein and daidzein inhibited ADP ( Figure 3 A), collagen ( Figure 3 B), thrombin ( Figure 3 C), and arachidonic acid ( Figure 3 D) induced platelet aggregation but also high concentration of collagen ( Figure 3 E) and integrin αIIbβ3 activator anti-αIIb TM ( Figure 3 F) induced platelet aggregation, suggesting these soy isoflavones might inhibit αIIbβ3 outside-in signaling [ 22 , 30 , 31 ]. The inhibitory effect of genistein and daidzein on platelet aggregation was not through GPIb-IX signaling, since both of these compounds inhibited ADP ( Figure 3 G) and collagen ( Figure 3 H) induced platelet aggregation in GPIbα deficit platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that 14-3-3ζ binds to the cytoplasmic domain of integrin β3 and facilitate outside-in signaling transduction [ 22 ]. Therefore, we investigated whether genistein and daidzein affect 14-3-3ζ-integrin β3 complex formation in platelet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether ZDPI affects integrin signaling transduction, we measured the phosphorylation of c-Src at Tyr 416 , which is caused by integrin activation and reflects the active state of c-Src. 29,30 Tyr 416 phosphorylation level of c-Src was increased during platelet activation (►Fig. 3D, E, line 2), while ZDPI inhibited this phosphorylation concentration-dependently in both PAR1AP and anti-αIIb TM treated platelets (►Fig.…”
Section: Zdpi Binds To Active-state Integrin αIibβ3mentioning
confidence: 99%
“…The binding of dalbavancin to ACE2 mutant proteins was measured by LC-MS/MS linked co-IP according to our previous method with a little modification. 36 Briefly, dalbavancin (10 μg, HY-17586, MedChemExpress), point mutated ACE2 (2 μg), anti-ACE2 antibody (1 μg, 10108-T60, Sino Biological), and protein A agarose (40 μl, 15918014, ThermoFisher) were incubated overnight at 4°C. After washing with PBS three times (5 min), dalbavancin was eluted with 70% ethanol and analyzed by LC-MS/MS.…”
Section: Cathepsin L Activity Assaymentioning
confidence: 99%